2022
DOI: 10.1108/ijopm-03-2021-0211
|View full text |Cite
|
Sign up to set email alerts
|

Organizing for permanent beta: performance measurement before vs performance monitoring after release of digital services

Abstract: PurposeDue to the complexity of digital services, companies are increasingly forced to offer their services “in permanent beta”, requiring continuous fine-tuning and updating. Complexity makes it extremely difficult to predict when and where the next service disruption will occur. The authors examine what this means for performance measurement in digital service supply chains.Design/methodology/approachThe authors use a mixed-method research design that combines a longitudinal case study of a European digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…, 2021; Mohapatra et al. , 2021; van Oorschot et al. , 2022); 2) implement knowledge management processes (KMPs) capable of identifying the necessary knowledge and disseminating it within the organisation (Leoni, 2015; Sutopoh et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021; Mohapatra et al. , 2021; van Oorschot et al. , 2022); 2) implement knowledge management processes (KMPs) capable of identifying the necessary knowledge and disseminating it within the organisation (Leoni, 2015; Sutopoh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing uncertainty and turbulent contexts might have significant repercussions on the manufacturing industry in terms of mandatory closures, logistics bottlenecks, supply difficulties and volatility in consumption trends (Ardolino et al, 2022). Indeed, in recent times, numerous research studies have demonstrated how the success and survival of manufacturing firms are closely linked to their ability to 1) embrace advanced digital technologies, such as artificial intelligence (AI) (Eloranta et al, 2021;Mohapatra et al, 2021;van Oorschot et al, 2022); 2) implement knowledge management processes (KMPs) capable of identifying the necessary knowledge and disseminating it within the organisation (Leoni, 2015;Sutopoh et al, 2021); and 3) put in place supply chain resilience (SCR) strategies to maintain satisfactory levels of performance in the short, medium and long terms (Belhadi et al, 2021a). In fact, these three elements (AI, KMPs and SCR)individually consideredpositively affect firm performance (Jallow et al, 2020;Li et al, 2017;Tan and Wong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rasool et al (2021Rasool et al ( , p. 1204) defined DSC as "a seamlessly interconnected transparent supply chain, that independently performs decision support activities to minimize human input needs". Studies have reported several benefits of DSC over the traditional supply chain, including improved transparency, speed, flexibility, productivity and profitability (Haoud and Hasnaoui, 2019;Oorschot et al, 2022). The list of these benefits expands when applied to a closed-loop supply chain.…”
Section: Digital Technologies and Supply Chainmentioning
confidence: 99%